4.03.005: Notebook: solo and duos, 1977 - Walsh, Don; Snider, Jamie (1977)
Some odds and ends of song charts. Page 14's The Cochrane and page 15's Howlin at the Moon are two songs I wrote. Gower Street blues was written by myself and Jamie Snider one lazy afternoon. The Cochrane was a pub we frequented as well as played at. One night I was asking a girl out and she told me she'd never have anything to do with me because I was only a "stud". Myself and Jamie wrote a funny ditty about the Gower Street Stud the next day. Gower Street was the street we lived on.